The solvent acidity effect on the gelation behavior on the Fe3+-urushi organogels - Yang, Eunyeong; Hwang, Seung Sang; Won, Jongok (Elsevier BV, 2023)
In this study, urushi organogels with high mechanical strength in different solvents were prepared with Fe3+ ions from urushiol extracted from natural lacquer sap. The organogels were fabricated by the polymerization of urushiol and physical crosslinking due to the formation of coordination bonds with trivalent Fe ions in the Fe/ urushiol solution. Trivalent Fe ions catalyze the polymerization of urushiol into urushi, which is a solution for uncontrollable laccase activity in traditional lacquer formation. The gelation and characteristics of urushi organogels in different solvents with different amounts of trivalent Fe ions were investigated. Urushiol is a mixture of catechol derivatives with long alkyl chains, and it is known that the polymerization of catechol and the formation of coordination bonds depends on acidity. Herein, the trivalent Fe/ethanol solution is more acidic than the acetone solution at the same concentration, which affects the chemical and physical bond formation in the urushi organogel. The effect of the solvent on the formation of the urushi organogels was investigated by Fourier transform infrared spectroscopy and Raman spectroscopy. Different amounts of chemical and physical crosslink sites in acetone-and ethanol-based organogels are found to result in different tensile strengths for freeze-dried gels, while the shear modulus values are consistent with each other. The stretchability and me-chanical strength can be controlled by simply changing the solvent used for the fabrication of Fe/urushi orga-nogels. The proposed Fe/urushi organogels broaden the possible scope for application of eco-friendly natural urushi.